2012
DOI: 10.1177/1010539511404397
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Associations Between Household-, Work-, and Leisure-Based Physical Activity and All-Cause Mortality Among Older Taiwanese Adults

Abstract: Most studies on the health effects of leisure time physical activity have focused on mortality. There has been limited research regarding physical activity undertaken at work or around the home and mortality. This study assessed the associations between leisure, work, and household physical activity and subsequent all-cause mortality among older adults aged 65 years and older (n = 2133) in Taiwan, over 8 years. Physical activity was evaluated with the Physical Activity Scale for the Elderly. Cox proportional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 26 publications
5
27
1
1
Order By: Relevance
“…However, previous study showed that older adults could be protected from all-cause mortality by doing housework, lawn work/yard care, caring for another person, or outdoor gardening. 5 We found that younger participants and those who were still working had significantly higher mean PASE-M score similar to the findings in the original study. 10 Consistent with others, 2,23 there was significant decline in physical activity levels with age.…”
Section: Comparison With Other Studiessupporting
confidence: 88%
See 1 more Smart Citation
“…However, previous study showed that older adults could be protected from all-cause mortality by doing housework, lawn work/yard care, caring for another person, or outdoor gardening. 5 We found that younger participants and those who were still working had significantly higher mean PASE-M score similar to the findings in the original study. 10 Consistent with others, 2,23 there was significant decline in physical activity levels with age.…”
Section: Comparison With Other Studiessupporting
confidence: 88%
“…Another interesting finding was household activity makes the largest contribution to total physical activity among the elderly as shown in this study and others. 5,10,13 Older adults in this study were less likely to engage in leisure time activities such as sport and recreational activities. However, previous study showed that older adults could be protected from all-cause mortality by doing housework, lawn work/yard care, caring for another person, or outdoor gardening.…”
Section: Comparison With Other Studiesmentioning
confidence: 77%
“…The literature on the relationship between physical activity and the reduction of mortality risk in older adults shows conflicting findings, both in terms of the existence of an association 11 , 12 , 28 and its strength. 9 , 10 , 29 These differences highlight the importance of investigating sex as a potential effect modifier of the relationship between physical activity and all-cause mortality in older adults. Studies have found similar findings to the results from the Bambuí cohort, which show a protective effect of physical activity only in older men.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have proved that it has positive influence on reducing mortality and the incidence of many diseases [4][5][6]. Regular physical activity also helps to maintain functional abilities which play a crucial role in self-reliance and motor resourcefulness in everyday life, contributing to having a positive self-esteem for the quality of life.…”
Section: Introductionmentioning
confidence: 99%